Situational Analysis: A Visual Analytic Approach that Unpacks the Complexity of Occupation. Issue 1 (2nd January 2016) - Aldrich, Rebecca; Laliberte Rudman, Debbie
Abstract : Concurrent with the development of a transactional perspective, the notion of "the situation" has increasingly been taken up in occupational science scholarship. Accordingly, research methodologies and approaches that capture the multifaceted elements of situations need to be explored. Situational analysis, pioneered by sociologist and grounded theorist Adele Clarke, shows promise for facilitating inquiries into situations of occupational engagement. In this article we review the situational analysis approach and provide an example of its application to research on the situation of long-term unemployment. In this application, situational mapping illuminated the contradiction of simultaneously being "activated" and "stuck". Situational analysis helped unpack how this contradiction was shaped within North American contexts. Based on this example and others outside the occupational science literature, we discuss how situational analysis can be a useful tool for fostering critical, socially-responsive, and community-engaged occupational science research.